Strategi Kepala Taman Kanak-Kanak dalam Persiapan Implementasi Konsep Merdeka Bermain - Nilamsari Kusumawati Putri; Jolaekha Jolaekha; Lita Latiana (Eduprof : Islamic Education Journal, 2022)
The principal has an important role in the progress of the school, the strategy that the principal has on the preparation for the application of independence is certainly an important thing to discuss. The purpose of this study is to know what strategies can be carried out by the principal in preparing for the application of the concept of independence. The study was conducted in the Principal of the Mutiara Bunda Kindergarten School in Cirebon Regency. Research uses descriptive qualitative methods and uses non-probablity sampling sampling techniques with a type of purposive sampling where the type of sample drawing technique is carried out with certain considerations and objectives. Data collection techniques in this study use data triangulation to measure the accuracy of data obtained. The results of this study are the principal's strategy in preparing for the application of independence playing in this school there are five main points, namely: understanding as a leader, example, open with new things, providing training to teachers in the school and evaluating programs- The new program is implemented so that it can quickly find the right solution to complete the existing obstacles. ABSTRAK Kepala Sekolah memiliki peran penting dalam kemajuan sekolah, strategi yang dimiliki Kepala Sekolah terhadap persiapan penerapan merdeka bermain tentunya menjadi satu hal yang penting utnuk dibahas. Tujuan penelitian ini adalah utnuk mengetahui strategi apa saja yang dapat dilakukan oleh Kepala Sekolah dalam mempersiapkan penerapan konsep merdeka bermain. Penelitian dilakukan pada Kepala Sekolah TK Mutiara Bunda Kabupaten Cirebon. Penelitian menggunakan metode kualitatif deskriptif serta menggunakan teknik pengambilan sampel nonprobablity sampling dengan jenis purposive sampling dimana jenis teknik mengambilan sampel ini dilakukan dengan pertimbangan dan tujuan tertentu. Teknik pengumpulan data dalam penelitian ini menggunakan triangulasi data untuk mengukur keakuratan data yahng didapat. Hasil dari penelitian ini adalah strategi kepala sekolah dalam persiapan penerapan merdeka bermain di sekolah ini terdapat lima poin utama, yaitu: pemahaman sebagai pemimpin, keteladanan, terbuka dengan hal baru, memberikan pelatihan kepada guru-guru yang ada di sekolah serta melakukan evaluasi terhadap program-program baru yang diterapkan sehingga dengan cepat dapat menemukan solusi yang tepat guna menyelesaikan hambatan yang ada.